Evaluation of Work Related Stress among Nurses in Some Selected Hospitals in Maiduguri, Borno State, Nigeria - Abdulsalam, Abdullah; Tijjani, S. A.; Gana, M. K.; Azeez, T. A.; Vurho, J. Z. (NIU Journal of Social Sciences; Vol 11 No 3 (2025): NIU Journal of Social Sciences, Vol. 11 No. 3, September 2025, 2025)
Workplace stress is the physical and emotional responses to situation that can happen when there is a conflict between job demands on the employee and the amount of control an employee has over meeting these demands. Work stress is comprised of the mental and physical conditions, which hurt the productivity, effectiveness, psychophysical health, work ability, satisfaction, and quality of work of individual workers in the workplace. Aim of this study is to assess frequency of stressful event among nurses and how stressful they perceived those events to be based on nine subscales of stress factors. This study adopted descriptive research design.  The population of this study is 1690 while 310 were selected as sample size. The instrument for this study is adapted version named Nursing Stress Scale (NSS) with 38 items and 9 subscales. The instrument uses 5-liket scale range from not at all stressful to extremely stressful. The instrument was validated for content and face validity by experts in the Department of Nursing Science University of Maiduguri and some senior nursing staff in University of Maiduguri Teaching Hospital. The reliability of the instrument was determined using Split-half reliability method among 18 nurses that were excluded from study. The reliability of the instrument is 0.71 which adjudge it reliable. Descriptive statistics of frequency counts, percentages and mean were used to analyze the data collected, while inferential statistics of independent t-test was used to test the hypothesis. The result showed that the leading stress factors among the nurses are; stress levels of death and dying stressors with mean (3.41) and S.D (1.25), stress levels of discrimination stressors with mean (3.34) and S.D (1.28), stress levels of uncertainty concerning treatment stressors with mean (3.35) and S.D (1.28) and stress levels of workload stressors with mean (3.44) and S.D (1.55). Moreover, the result of this study showed that no significant difference exists in dying and death of patients among nurses in some selected hospitals in Maiduguri based on gender (P>0.05). It was concluded that job-related stress among nurses in selected Maiduguri hospitals was high. Then, it was recommended that organizations/ hospitals that employ nurses should organize programs/ seminars to monitor and manage stress especially regarding staff issues and job demands. Keywords: Work related, Stress, Nurses.